2013
DOI: 10.3109/01902148.2013.829537
|View full text |Cite
|
Sign up to set email alerts
|

High-fat diet promotes lung fibrosis and attenuates airway eosinophilia after exposure to cockroach allergen in mice

Abstract: Obesity is an important risk factor for asthma but the mechanistic basis for this association is not well understood. In the current study, the impact of obesity on lung inflammatory responses after allergen exposure was investigated. C57BL/6 mice maintained on a high-fat diet (HFD) or a normal diet (ND) after weaning were sensitized and challenged with cockroach allergen (CRA). Airway inflammation was assessed based on inflammatory cell recruitment, measurement of lung Th1-Th2 cytokines, chemokines, eicosanoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 54 publications
1
41
0
1
Order By: Relevance
“…In a high-fat diet-ovalbumin model, airway reactivity was inhibited by blocking tumor necrosis factor-a and by depleting macrophages (44), suggesting a critical role for macrophage production of tumor necrosis factor-a in airway reactivity in obese allergic mice. In another study, highfat diet-induced obesity was associated with increased collagen deposition in the lung (even before allergen challenge), whereas a cockroach allergen challenge in obesity was associated with decreased prostaglandin E2 (a bronchodilator) compared with lean mice (34). These studies show that obesity, induced through dietary or genetic means, can alter baseline airway structure, increase allergen-induced airway inflammation, and increase airway reactivity in allergic airway disease.…”
Section: Pre-existing Asthma Complicated By Obesitymentioning
confidence: 79%
See 1 more Smart Citation
“…In a high-fat diet-ovalbumin model, airway reactivity was inhibited by blocking tumor necrosis factor-a and by depleting macrophages (44), suggesting a critical role for macrophage production of tumor necrosis factor-a in airway reactivity in obese allergic mice. In another study, highfat diet-induced obesity was associated with increased collagen deposition in the lung (even before allergen challenge), whereas a cockroach allergen challenge in obesity was associated with decreased prostaglandin E2 (a bronchodilator) compared with lean mice (34). These studies show that obesity, induced through dietary or genetic means, can alter baseline airway structure, increase allergen-induced airway inflammation, and increase airway reactivity in allergic airway disease.…”
Section: Pre-existing Asthma Complicated By Obesitymentioning
confidence: 79%
“…Consumption of a high-fat diet during gestation could contribute to the development of asthma in offspring. A high-fat diet can also alter lung structure in adult mice: structural changes are present in the airway epithelium of adult mice fed a high-fat diet (33), and collagen content in the lungs and airways is increased (34). A high-fat diet at any time from in utero development to adulthood could lead to structural and functional changes in the airway wall that could contribute to the airway disease of obesity.…”
Section: Asthma Caused By Obesitymentioning
confidence: 99%
“…In addition, it is shown that high saturated fat intake from a "meat and dimsum" dietary pattern was associated with an increased risk for incident cough with phlegm (Butler et al, 2006). An animal study also showed that a high fat diet may cause lung inflammation and incident lung fibrosis by increasing specific profibrotic factors (Ge et al, 2013) that potentially aggravate lung function. In this study, the proportion of fat intake from total energy was 14.2 ± 0.1% of total calorie intake, which is within the reference range and relatively lower compared with that in Western societies.…”
Section: Modelmentioning
confidence: 97%
“…The model of obesity and the genetic background of the mice modify the relationship between allergic airway disease and adiposity (13). In the current article, a high-fat diet increased allergic airway inflammation, whereas other investigators, using a different model, have reported that a high-fat diet decreases allergic airway inflammation (14,15). Key data suggesting that the work by Ahangari and colleagues has direct relevance for human disease came from the inclusion of a case-control study showing that the human homolog of Chi3l1 (YKL-40) was increased in the serum of patients with persistent asthma and correlated with truncal obesity and low lung function (the latter only in obese patients with asthma).…”
Section: A Common Pathway To Obesity and Allergic Asthmamentioning
confidence: 50%